PERUBAHAN POLA MENGHISAP NYAMUK AKIBAT DEFORESTASI HUTAN: TINJAUAN SISTEMATIS - Suharno Zen; Miftahuz Zakiyah; Nadya Syarifatul Fajriyah; Ilham Fathurrahman (Jurnal Sains Biomedis, 2026)
Deforestation is a form of environmental change that significantly impacts the ecology of disease vectors, including mosquitoes. Changes in forest cover can influence mosquito behavior, particularly biting patterns and host preferences, which have implications for increasing the risk of vector-borne diseases in humans. The purpose of this article is to systematically review research findings from the past three years related to changes in mosquito biting patterns due to deforestation. The method used was a systematic review of scientific articles published between 2022 and 2026, which discussed the relationship between deforestation, habitat change, and mosquito biting behavior. The results indicate that deforestation contributes to increased mosquito biting activity on humans, changes in peak biting times, and a shift in host preference from animals to humans. The conclusions of this review confirm that deforestation plays a significant role in changing mosquito behavior and has the potential to increase the risk of vector-borne disease transmission.